Multi-Omics Profiling of Hepatocellular Carcinoma Reveals Prognostic Biomarkers, HBV-Driven Oncogenic Networks, and Therapeutic Vulnerabilities in Genomic-Immune Crosstalk - Angoma-Sindani, Blaise; Mwata-Velu, Tat'y; Mavuela Maniansa, Richard; Milomba Velu, Rachel; Tshibangu-Mbuebue, Blaise; Qasim, Ayesha; Mbungu Baptista, Aidor; M. Migabo, Emmanuel (Universitas Airlangga, 2026)
Introduction: Hepatocellular carcinoma (HCC) remains a molecularly heterogeneous malignancy with limited therapeutic biomarkers. While transcriptomic studies have identified dysregulated genes, their prognostic relevance, proteomic concordance, and interactions with hepatitis B virus (HBV) mutations remain underexplored. Methods: We integrated multi-omics analyses of two independent HCC cohorts (GEO datasets), proteomic profiling, survival data, HBV mutation associations, immune cell infiltration, drug sensitivity (GDSC), and genomic alteration patterns to define drivers of HCC progression. Results: We identified 23 genes, including AURKA, CDK1, MKI67, linked to poor survival and genomic instability, and three protective genes (PLVAP, GSTA4, GREB1). HBV mutations (PreS, A1762T/G1764A) correlated with elevated expression of proliferative (TOP2A, RRM2) and metabolic (SQLE) genes, particularly in genotype C HCC. Despite minimal pathological stage variation, tumors exhibited robust cell cycle/EMT pathway activation (ASPM, CCNB1), highlighting molecular heterogeneity. Proliferative genes paradoxically associated with regulatory immune subsets (B cells, nTregs) and immunosuppression. Drug sensitivity analysis revealed ASPM and STMN1 as therapeutic vulnerabilities, while SPP1 and PRKAA2 marked resistance. Genomic profiling confirmed frequent mutations/CNAs in poor-prognosis genes (MKI67, CDKN2A) and stability in protective genes. Conclusion: This study establishes a multi-omics framework linking HBV-driven oncogenesis, genomic instability, and immune evasion to HCC progression. Prognostic signatures and pathway activation patterns advocate for molecular subtyping to complement clinical staging. The dual association of proliferative genes with immune suppression and drug sensitivity highlights opportunities for combinatorial therapies targeting oncogenic drivers (CDK1, ASPM) and immune checkpoints. These findings advance precision oncology strategies in HBV-associated HCC.